THE QUALITY OF ENVIRONMENTAL PERFORMANCE ASSESSED FROM GREEN ACCOUNTING IMPLEMENTATIONS IN COMPANIES IN INDONESIA (Ekspektra : Jurnal Bisnis dan Manajemen, 2022)
This study is dedicated to making a description of the quality of environmental performance in terms of the implementation of green accounting in companies in Indonesia. Sources of data used in this study are data from scientific papers related to research problems as well as from previous research. This study uses an analytical method in the form of a literature review with the help of the MAXQDA 2020 software. The results of this study prove that companies that implement and report their environmental performance or green performance in environmental reporting or green accounting in Indonesia have an influence on the company's image in the eyes of company stakeholders. Companies that report clearly and correctly their environmental performance can make users of this information aware of the company's economic and environmental performance. This information, if published, will provide various benefits in accordance with the explanation in this study, namely the quality of environmental performance in terms of the implementation of green accounting in companies in Indonesia. Most companies in Indonesia only fulfill one indicator of the implementation of green accounting, namely the presentation of costs associated with corporate waste management in the financial statements so that the company's environmental performance can only be seen through the projected numbers in the overall accounting concept. The quality of environmental performance reporting or green performance in environmental reporting or green accounting by companies in Indonesia is still not good enough, seen from the lack of environmental performance reporting by certain companies. Companies that record their environmental performance and publish these reports properly and correctly tend to have a positive image in the eyes of stakeholders.reporting by certain companies. Companies that record their environmental performance and publish these reports properly and correctly tend to have a positive image in the eyes of stakeholders.